Systematic review and classification of: TIBIR - Breif Parent training in Norway (2. ed.) - Eng, Helene; Patras, Joshua; Handegård, Bjørn Helge (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2015)
Background: This article is a summary of current knowledge of the effects of the Early Intervention for Children at Risk (TIBIR) – Brief Parent training in Norway. TIBIR – Brief Parent Training is a short-term parent training intervention of 3-5 sessions. The target group is families with children between 3-12 years old showing signs of, or are at risk of developing behavioral problems. The short intervention is one of six interventions in the program package, TIBIR. The Norwegian Center for Child Behavioral Development is the developer and purveyor of TIBIR. Method: The following databases were used to find published articles about the TIBIR intervention: Embase, Medline and Psycinfo, NORART Cochrane, Cristin, NORA, SCOPUS and SweMed. Two articles about the Brief Parent Training intervention were included in the review. Results: The results include a summary of the project's description, the outcome of the efficacy studies, methodological quality of the research, and implementation quality. TIBIR – Brief Parent Training is very well described in several documents including a detailed manual. There is a single Nordic RCT efficacy study with measurements pre-post and 6 months post-treatment. The effectiveness study was conducted with a high degree of scientific rigor, and the intervention showed positive outcomes for the group who received TIBIR. The effects of TIBIR are considered to be of practical and statistical significance. The intervention has good systems to ensure implementation quality, which makes it likely that the positive results from the study can be replicated in usual practice. Conclusion: Although the measure satisfies the requirements for the highest levels of evidence in almost all areas, independent studies and replication are necessary in order to conclude that the intervention has the strongest evidence of efficacy. TIBIR- brief intervention classified evidence Level 4 – Intervention with satisfactory evidence of efficacy. The article is a revision of a previous description of the intervention that was published previously in Ungsinn (Mørch, 2012); the review has been revised to conform to new Ungsinn scoring criteria and procedures.